항공사 간 조인트벤처의 경쟁법적 규제에 관한 연구 - 이호영 (법학논총, 2019)
1990년대 이후 우리나라 항공사를 포함한 각국의 주요 항공사들은 세계 항공시장의 급격한 변화에 대응하기 위해 적극적으로 다른 항공사와 제휴협정을 체결하고 있다. 항공사 간 제휴협정은 가장 낮은 단계의 노선 연결서비스 약정으로부터 수입과 비용 또는 이익을 공유하는 조인트벤처와 같이 합병과 유사한 통합까지 다양한 수준에서 이루어진다. 항공사 간 제휴협정은 경쟁법상 가격담합이나 입찰담합과 구분되는 전형적인 연성 공동행위로서 범위의 경제 등 효율성 증진효과가 그로 인한 경쟁제한적 효과를 상쇄할 개연성이 큰 것으로 이해되고 각국 경쟁법제에서 별다른 문제없이 허용되었다. 그러나 근래 항공사들이 체결하는 조인트벤처는 한편으로 효율성 증진효과를 기대할 수 있지만, 다른 한편으로 상당한 정도의 경쟁제한적 우려를 낳고 있는데 특히, 해당 노선에서 유력한 지위를 차지하고 있는 항공사 간 조인트벤처에 대해서는 심각한 경쟁제한적 우려가 제기될 수 있다. 항공사 간 조인트벤처를 심사함에 있어서 중요한 것은 해당 항공사 간 코드 쉐어나 낮은 수준의 협력약정을 통해서 실현할 수 있는 효율성이나 소비자 편익 이외에 조인트벤처와 같은 높은 수준의 통합을 통해서만 달성할 수 있는 추가적인 효율성과 소비자 편익이 존재하는지 확인하고, 이를 조인트벤처로 인하여 우려되는 경쟁제한 효과와 비교‧형량하는 것이다. 항공사 간 조인트벤처로 인하여 심각한 경쟁제한 효과가 우려되는 경우에는 조인트벤처를 통해 기대할 수 있는 소비자 편익을 유지하면서도 경쟁제한 효과를 억제하기 위해, 반드시 조인트벤처 자체를 전면적으로 금지하지 않더라도 해당 노선을 조인트벤처의 범위에서 제외시키거나 허브공항의 슬롯 중 일부를 신규로 진입하는 경쟁 항공사에 제공하도록 하는 등의 조건을 부과할 필요가 있다. Since the 1990s, major airlines, including Korean airlines, have actively entered into alliance agreements with other airlines to cope with the rapid changes in the global aviation market. Alliance agreements between airlines are at various levels, ranging from the lowest-level interlining service agreement to merger-like integration, such as joint ventures that share revenues and costs, or benefits. The alliance agreement between airlines is a typical non-hardcore collaborative act that is distinguished from price fixing or bid rigging under the competition law. It is generally accepted that the efficiency enhancement effect such as economies of scope is likely to offset the anticompetitive effect, in case of the airline alliance agreement. However, many joint ventures that have recently been signed by airlines create a considerable degree of anticompetitve concern. In particular, the joint venture among airlines, which hold a strong market position on the route can raise serious anticompetitive concerns. In reviewing a joint venture between airlines, it is important to evaluate the added efficiency and consumer benefits that can only be achieved through such high level integration, in addition to them which can be achieved through ordinary code sharing or low-level alliance between carriers, and to compare them with its anticompetitive effect. In the event that a joint venture between airlines is likely to cause serious anticompetitive effect, remedies such as carve-outs and/or slot divestitures may be effective to realize the consumer benefits expected from the joint venture but to prevent its anticompetitive effect.
Keywords: 항공사 제휴협정; 조인트벤처; 경쟁자 간 협력; 메탈 중립성; 항공사업법; 독점금지법 적용면제; Airline alliances; Joint ventures; competitor collaborations; metal-neutrality; Air Transportation Business Act; Antitrust Immunity